The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1371/journal.pone.0100114
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Relationship between Physicians and the Pharmaceutical Industry in a Public General Hospital in Lima, Peru

Abstract: BackgroundThe interaction between physicians and the pharmaceutical industry influences physicians' attitudes and prescribing behavior. Although largely studied in the US, this topic has not been well studied in resource-poor settings, where a close relationship between physicians and industry still exists.ObjectiveTo describe physician interactions with and attitudes towards the pharmaceutical industry in a public general hospital in Lima, Peru.DesignDescriptive, cross-sectional study through an anonymous, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 21 publications
(38 reference statements)
4
53
1
3
Order By: Relevance
“…Eight of these articles focused on physicians’ attitudes and views regarding physician-PR interactions [9, 2127]; four focused on the nature of the interaction [26, 2830]; two concentrated on the frequency of these interactions [31, 32]; and two focused on the reasons behind such interactions [33, 34]. The detailed themes and extracted text is presented in Additional file 3.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eight of these articles focused on physicians’ attitudes and views regarding physician-PR interactions [9, 2127]; four focused on the nature of the interaction [26, 2830]; two concentrated on the frequency of these interactions [31, 32]; and two focused on the reasons behind such interactions [33, 34]. The detailed themes and extracted text is presented in Additional file 3.…”
Section: Resultsmentioning
confidence: 99%
“…Lieb et al reported that 77.0% (n = 160) of German respondents met with PRs at least once a week, and 19.0% (n = 39) were visited by PRs on a daily basis [29]. Other studies also reported that PRs visit physicians regularly in order to promote their products [9, 21, 22, 26, 29, 32]. De Ferrari et al studied the relationship between the specialty of the prescriber and the frequency of PR visits [9].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This can in turn undermine patients' well-being and finances. Furthermore, physicians are not completely aware of the influence of pharmaceutical marketing on their own prescription patterns, but they seem to recognize other physicians' prescribing patterns (De Ferrari, Gentille, Davalos, Huayanay, & Malaga, 2014). As reported by Kisa (2006), there is a balance to be struck between maximizing effectiveness, minimizing risks and costs and prescribing appropriately while respecting patients' choices.…”
Section: Pharmaceutical Marketing Techniquesmentioning
confidence: 99%